STUDI TENTANG BUDAYA KERJA KEPOLISIAN DALAM PELAYANAN TERHADAP MASYARAKAT DI LINGKUNGAN POLSEKTA SUNGAI KUNJANG KECAMATAN SUNGAI KUNJANG KOTA SAMARINDA - Awarrinda, Fitriani (PREDIKSI, 2014)
Seeing the importance of implementing a culture of police work in the service society, which is when the service is done in accordance with the procedures and possess good communication between the community and police officers, it will be the creation of quality police services more transparent and clean of course. Thus encouraging writers to do research on police work culture in the public service, especially service to public complaints. In terms of receiving complaints and reports from the public, particularly police officers sued the police Service Center must be able to communicate with the complainant/victim.